2021
DOI: 10.1007/s00170-021-08343-1
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and corrosion resistance of stainless steel produced by bypass coupling twin-wire indirect arc additive manufacturing

Abstract: This study investigates the application of bypass coupling twin-wire indirect arc welding (BC-TWIAW) in arc additive manufacturing of 18-8 stainless steel. It is found that the droplet transfer changed from short circuit mode to stable spray mode with the welding current rising. Droplet transfer was the most stable when welding current was 200 A. Compared with the conventional MIG welding arc additive manufacturing, the efficiency of BC-TWIAW additive manufacturing can be increased by more than 30%. Electroche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 30 publications
(31 reference statements)
0
15
0
Order By: Relevance
“…The study observed 33 a transition in droplet transfer behavior for BC-TWIAW samples from a short-circuit mode to a stable spray mode as the welding current increased. Notably, the most stable droplet transfer occurred at a welding current of 200 A.…”
Section: (4) Corrosion Of Wire Arc Additively Manufactured Steelsmentioning
confidence: 91%
See 2 more Smart Citations
“…The study observed 33 a transition in droplet transfer behavior for BC-TWIAW samples from a short-circuit mode to a stable spray mode as the welding current increased. Notably, the most stable droplet transfer occurred at a welding current of 200 A.…”
Section: (4) Corrosion Of Wire Arc Additively Manufactured Steelsmentioning
confidence: 91%
“…59 (4.2.8) Process modification. In a study, We et al 33 employed bypass coupling twin-wire indirect arc welding (BC-TWIAW) for arc additive manufacturing of 18-8 stainless steel. In twin-wire indirect arc welding, the negative and positive poles of the DC power source are connected to the two feeding wires.…”
Section: (4) Corrosion Of Wire Arc Additively Manufactured Steelsmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach resulted in a 20% less height deviation with an enhanced material utilisation by 13% due to the bypass current generation, which reduced the heat input onto the substrate. In a significant study, Wu et al (2022) developed a bypass coupled twin-wire indirect arc welding for AM. This approach was found to be 30% more efficient than conventional GMAW-WAAM.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the “Teach-Playback” mode [ 3 ] is widely used in robot welding, resulting in a more favorable working environment; it increases welding efficiency to some extent and ensures the consistency of welding quality. However, the “Teach-Playback” mode still relies on the worker’s judgment for determining the welding start point and welding mode.…”
Section: Introductionmentioning
confidence: 99%